Association between liver-type fatty acid-binding protein and hyperuricemia before and after laparoscopic sleeve gastrectomy - You, Hui; Ma, Huihui; Wang, Xingchun; Wen, Xin; Zhu, Cuiling; Mao, Wangjia; Bu, Le; Zhang, Manna; Yin, Jiajing; Du, Lei; Cheng, Xiaoyun; Chen, Haibing; et al. (Frontiers in Endocrinology, 2022)
Background: Liver-type fatty acid-binding protein (FABP1) contributes to metabolic disorders. However, the relationship between FABP1 and hyperuricemia remains unknown. We aimed to evaluate the correlation between serum FABP1 and hyperuricemia in patients with obesity before and after laparoscopic sleeve gastrectomy (LSG). Methods: We enrolled 105 patients (47 men and 58 women) with obesity who underwent LSG. They were divided into two groups: normal levels of uric acid (UA) (NUA, n = 44) and high levels of UA (HUA, n = 61) with matching sexes. FABP1 levels and other biochemical parameters were measured at baseline and 3, 6, and 12 months after LSG. Results: Serum FABP1 levels were significantly higher in the HUA group than in the NUA group (34.76±22.69 ng/ mL vs. 25.21±21.68 ng/mL, P=0.024). FABP1 was positively correlated with UA (r=0.390, P=0.002) in the HUA group. The correlation still existed after adjusting for confounding factors. Preoperative FABP1 levels were risk factors for hyperuricemia at baseline. UA and FABP1 levels decreased at 3, 6, and 12 months postoperatively. FABP1 showed a more significant decrease in the HUA group than in the NUA group at 12 months (27.06±10.98 ng/mL vs. 9.54±6.52 ng/mL, P=0.003). Additionally, the change in FABP1 levels positively correlated with changes in UA levels in the HUA group 12 months postoperatively (r=0.512, P=0.011). Conclusions: FABP1 was positively associated with UA and may be a risk factor for hyperuricemia in obesity. FABP1 levels were higher but decreased more after LSG in obese patients with hyperuricemia than in those without hyperuricemia.